Evaluation of Bacterial Spot Disease of Capsicum annuum L. in Drought Stress Environment by High Temperature - Jong-Ok Jang; Byung-Hyuk Kim; Jung-Bok Lee; Jae-Ho Joa; Sangwook Koh (Research in Plant Disease, 2019)
The global warming by increased CO2 will effect of plant pathogenic microorganisms and resistance of host plants, and it is expected to affect host-pathogen interactions. This study used Capsicum annuum L. and Xanthomonas euvesicatoria, a pathogenic bacteria of pepper, to investigate interactions between hosts and pathogens in a complex environment with increased cultivation temperature and drought stress. As a result, the bacterial spot disease of C. annuum L. caused by X. euvesicatoria was 35°C higher than 25°C. In addition, the effect on water potential on bacterial spot disease was much greater water potential -150 kPa than -30 kPa. The disease progress and severity higher than water potential -30 kPa. This result will useful for understanding interaction with red pepper and X. euvesicatoria under the complex environment with increased cultivation temperature and in water potential -150 kPa drought stress in the future.